Some recently rediscovered analyses of Chinese bronzes from Oxford - Pollard, A; Rawson, J; Liu, R (Wiley, 2018)
We report here the rediscovery of the chemical analyses of approximately 540 Chinese bronze objects, carried out in RLAHA in the late 1950s by optical emission spectrometry. Although largely of historical interest, they do in fact even now approximately double the number analyses of Chinese bronze objects which contain data on both major and minor elements. In fact, the other major equivalent data set from the Freer Gallery and the Sackler Collection are of approximately the same vintage. We attempt to evaluate the quality of the data, and address a controversy which appeared in the literature during the 1960s and 1970s about the value of arsenic measurements in Chinese bronzes as an indicator of authenticity.